Promiscuous targeting of bromodomains by Bromosporine identifies BET proteins as master regulators of primary transcription response in leukemia - Picaud, S; Leonards, K; Lambert, J; Dovey, O; Wells, C; Fedorov, O; Monteiro, O; Fujisawa, T; Wang, C; Lingard, H; Tallant, C; Nikbin, N; et al. (American Association for the Advancement of Science, 2016)
Bromodomains (BRDs) have emerged as compelling targets for cancer therapy. The development of selective and potent BET inhibitors and their significant activity in diverse tumor models has rapidly translated into clinical studies and has motivated drug development efforts targeting non-BET BRDs. However, the complex multidomain/subunit architecture of bromodomain protein complexes complicates predictions of consequences of their pharmacological targeting. To address this issue we developed a promiscuous bromodomain inhibitor (bromosporine, BSP) that broadly targets BRDs (including BETs) with nanomolar affinity, creating a tool for the identification of cellular processes and diseases where BRDs have a regulatory function. As a proof of principle we studied the effect of BSP in leukemic cell-lines known to be sensitive to BET inhibition and found as expected strong anti-proliferative activity. Comparison of the modulation of transcriptional profiles by BSP at short inhibitor exposure resulted in a BET inhibitor signature but no significant additional changes in transcription that could account for inhibition of other BRDs. Thus, non-selective targeting of BRDs identified BETs, but not other BRDs, as master regulators of a context dependent primary transcription response.